Comparison of health and economic impacts of PM2.5 and ozone pollution in China. (September 2019) - Xie, Yang; Dai, Hancheng; Zhang, Yanxu; Wu, Yazhen; Hanaoka, Tatsuya; Masui, Toshihiko
Abstract: Many studies have reported associations between air pollution and health impacts, but few studies have explicitly differentiated the economic effects of PM2.5 and ozone at China's regional level. This study compares the PM2.5 and ozone pollution-related health impacts based on an integrated approach. The research framework combines an air pollutant emission projection model (GAINS), an air quality model (GEOS-Chem), a health model using the latest exposure-response functions, medical prices and value of statistical life (VSL), and a general equilibrium model (CGE). Results show that eastern provinces in China encounter severer loss from PM2.5 and more benefit from mitigation policy, whereas the lower income western provinces encounter severer health impacts and economic burdens due to ozone pollution, and the impact in southern and central provinces is relatively lower. In 2030, without control policies, PM 2.5 pollution could lead to losses of 2.0% in Gross Domestic Production (GDP), 210 billion Chinese Yuan (CNY) in health expenditure and a life loss of around 10, 000 billion, while ozone pollution could contribute to GDP loss by 0.09% (equivalent to 78 billion CNY), 310 billion CNY in health expenditure, and a life loss of 2300 billion CNY (equivalent to 2.7% of GDP). By contrast, with control policies, the GDP and VSLs loss in 2030 attributable to ambient air pollution could be reduced significantly. We also find that the health and economic impacts of ozone pollution are significantly lower than PM2.5, but are much more difficult to mitigate. The Chinese government should promote air pollution control policies that could jointly reduce PM2.5 and ozone pollution. Highlights: PM2.5 and ozone pollution-related health and economic impacts are compared. An integrated economy-air pollution-health assessment framework is adopted. Without control PM2.5 and ozone pollution may cause 2.0% and 0.09% GDP loss in 2030. Benefits of controlling ambient air pollution would be huge all over China.